Assessment of hypoxia, sedation level, and adverse events occurring during inhalation sedation using preadjusted mix of 30% nitrous oxide + 70%oxygen - P V Samir; Srinivas Namineni; P Sarada (Wolters Kluwer Medknow Publications, 2017)
Purpose: To assess the efficacy of nitrous oxide (N2O)-oxygen (O2) inhalation sedation by rapid induction technique using preadjusted mix of 30% N2O and 70% O2 in children. Materials and Methods: Sixty children with a treatment plan which included pulp therapy were recruited for the study. Children categorized 3 and 4 of Frankl behavior rating scale and American Society of Anesthesiologists health status I and II were included for the study. Children were distributed into study group (Group-I) and control group (Group-II) by fishbowl randomization. Children in Group-I were induced inhalation sedation using a preadjusted mix of 30% N2O and 70% O2 through rapid induction technique, and children in Group-II were exposed to inhalation sedation by conventional slow induction technique. Parameters such as least oxygen saturation, sedation levels by Richmond Agitation-Sedation Scale, time taken to achieve ideal sedation, maximum N2O concentrations used, and adverse events were recorded and evaluated for each procedure. Data were analyzed using independent sample t-test and Chi-square tests. Results: Analysis of data showed statistically significant difference between both groups in time taken to achieve ideal sedation (P < 0.001). No significant difference was seen in incidence of hypoxia (P < 0.512), maximum N2O concentrations used (P < 0.118), and occurrence of any adverse events. Conclusion: None of the children from both groups exhibited hypoxia. Sense of detachment was seen in one child each from both groups. Rapid induction by preadjusted mix resulted in ideal sedation in 57% children of the Group-I; rest had achieved these levels at 40% N2O. There was a significant difference in the time taken to achieve ideal sedation by rapid induction which was almost half the time taken with slow induction.